The Development of the Use of Persona Deixis in Early Childhood Speech in Instagram Reels @verenaindha: Pragmatic Study - Andini Dara Ananti; Nurlaksana Eko Rusminto; Sumarti (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study aims to describe the forms of personal deixis usage, analyze their appropriateness in speech context, and explain the phenomenon within a pragmatic framework. The research was conducted virtually on Instagram, particularly on the @verenaindha account, with data collected progressively from earlier to recent posts representing the child’s developmental stages. The population consisted of all child utterances in Reels content, while the sample included utterances produced by a child named Nala aged 22 months to approximately 5 years that contain personal deixis elements. The research instrument was the researcher supported by documentation and transcription techniques. Data were analyzed using an interactive model, including data reduction, data display, and conclusion drawing within a pragmatic approach. The results indicate that personal deixis usage develops gradually from non-deictic forms to more complex and contextually appropriate deictic forms. At the early stage, the child used proper names to refer to herself instead of first-person pronouns. This was followed by the use of kinship terms before eventually acquiring pronouns such as “I,” “you,” “he/she,” and “we.” This progression reflects the development of pragmatic competence, although inconsistencies still occur in certain situations. Furthermore, a distinction was found between linguistic accuracy and sociopragmatic appropriateness, particularly in the use of “I–you” forms toward parents. Overall, the development of personal deixis is influenced by cognitive factors and social environment.